Analysis of differentiated learning with problem-based learning model to improve learning activity - Evi Ariyanti Marlina Sihombing; Dede Ruslan; Wildansyah Lubis (Inovasi Kurikulum, 2025)
Elementary school learning often fails to optimally accommodate students’ learning styles, potentially hindering their participation and comprehension. This study aims to analyze the implementation of differentiated learning based on learning styles through the Problem-Based Learning (PBL) model to improve students’ learning activity in primary education. A descriptive qualitative approach was employed, involving a teacher and sixth-grade students from SDN 104246 Jati Baru as research subjects. Data were collected through observation, interviews, and documentation, and analyzed descriptively using data reduction, data display, and conclusion drawing. The findings indicate that implementing differentiated learning strategies with the PBL model enhances students’ active participation, confidence, and responsibility throughout the learning process. Student engagement increased when the instruction was tailored to their individual learning styles: visual, auditory, or kinesthetic. Furthermore, the teacher reported greater ease in managing the class fairly and adaptively. These results demonstrate that the integration of differentiated learning and the PBL model is not only theoretically relevant but also empirically effective in fostering inclusive and meaningful learning. The study recommends continuous teacher training in applying differentiation strategies and developing contextual, flexible instructional materials.   Abstrak Pembelajaran di tingkat sekolah dasar dengan gaya belajar peserta didik sering kali belum diakomodasi secara optimal, sehingga berpotensi menghambat partisipasi dan pemahaman mereka. Penelitian ini bertujuan untuk menganalisis penerapan pembelajaran berdiferensiasi berbasis gaya belajar dengan model Problem Based Learning (PBL) dalam meningkatkan aktivitas belajar peserta didik sekolah dasar. Pendekatan yang digunakan adalah kualitatif deskriptif dengan subjek penelitian terdiri dari guru dan peserta didik kelas VI SDN 104246 Jati Baru. Teknik pengumpulan data mencakup observasi, wawancara, dan dokumentasi, sedangkan analisis data dilakukan secara deskriptif melalui reduksi, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan strategi pembelajaran berdiferensiasi dengan model PBL mampu meningkatkan partisipasi aktif, rasa percaya diri, dan tanggung jawab peserta didik selama proses pembelajaran berlangsung. Peserta didik menunjukkan keterlibatan yang lebih tinggi ketika pembelajaran disesuaikan dengan gaya belajar mereka, baik visual, auditori, maupun kinestetik. Selain itu, guru juga merasakan kemudahan dalam mengelola kelas secara adil dan adaptif. Temuan ini menunjukkan bahwa integrasi pembelajaran berdiferensiasi dan model PBL tidak hanya relevan secara teoritis, tetapi juga efektif secara empiris dalam menciptakan pembelajaran yang inklusif dan bermakna. Penelitian ini merekomendasikan perlunya pelatihan guru dalam menerapkan strategi diferensiasi serta pengembangan perangkat ajar yang kontekstual dan fleksibel. Kata Kunci: aktivitas belajar; gaya belajar; pembelajaran berdiferensiasi; pembelajaran berbasis masalah